2016
DOI: 10.1038/srep38501
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Dysregulation of Women with Premenstrual Syndrome

Abstract: The aim of the current study was to test whether women with premenstrual syndrome (PMS) had difficulties in emotion regulation. In Study 1, we investigated the relationship between the habitual use of emotion-regulation strategies and the severity of PMS (n = 230). The results showed that the severity of PMS was negatively associated with the habitual use of reappraisal, but positively associated with the habitual use of suppression. In Study 2, we first investigated the difference in the spontaneous use of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 42 publications
1
16
0
2
Order By: Relevance
“…A score of 6-10 indicated mild PMS, 11-20 indicated moderate PMS, and more than 20 indicated severe PMS. The Cronbach's alpha = 0.80 in Wu et al (29) and 0.91 in the present study. Furthermore, the scale was deemed valid in differentiating women with PMS from those without PMS (21,(29)(30)(31) and reflected PMS severity (32,33).…”
Section: Pms Scalesupporting
confidence: 49%
“…A score of 6-10 indicated mild PMS, 11-20 indicated moderate PMS, and more than 20 indicated severe PMS. The Cronbach's alpha = 0.80 in Wu et al (29) and 0.91 in the present study. Furthermore, the scale was deemed valid in differentiating women with PMS from those without PMS (21,(29)(30)(31) and reflected PMS severity (32,33).…”
Section: Pms Scalesupporting
confidence: 49%
“…As physiological measures have been shown to discriminate between negative and positive emotional states (Levenson et al, 1990;Bradley and Lang, 2000;Kreibig, 2010), we aimed for distinguishing between positive and negative target emotions in our analyses. Only 13 studies in total (Gross and Levenson, 1997;Demaree et al, 2004;Ohira et al, 2006;Giuliani et al, 2008;Driscoll et al, 2009;Gross, 2011, 2015;Gruber et al, 2014;Baur et al, 2015;Gomez et al, 2015;Wu et al, 2016;Kotwas et al, 2019) induced positive emotions. Combinations of psychophysiological measure and emotion regulation strategy resulted in a maximum of three studies.…”
Section: Discussionmentioning
confidence: 99%
“…Premenstrual syndrome (PMS) is a menstrual-related disorder, which refers to a series of cyclical and relapsing physical, emotional, and cognitive symptoms that regularly recur during the late luteal phase of each menstrual cycle ( Ryu and Kim, 2015 ; Wu et al, 2016 ). Studies have shown that PMS is closely related to impaired stress reaction ( Hamaideh et al, 2014 ; Klatzkin et al, 2014 ; Tamaki Matsumoto, Ushiroyama, Kimura, Hayashi and Moritani, 2007 ; Sadler et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%